A multidimensional appraisal of domestic investment, external debt and economic development nexus: evidence from SSA - Gildas Dohba Dinga; Dobdinga Cletus Fonchamnyo; Nges Shamaine Afumbom (Journal of Business and Socio-Economic Development, 2025)
Purpose – This study examines the effect of external debt and domestic capital formation on economic development in Sub-Saharan African (SSA) economies. Design/methodology/approach – Using the Dynamic Common Correlation Effects (DCCE) technique and the Driscoll and Kraay fixed-effect technique, this paper conducts a multidimensional assessment of external debt and domestic investment on economic development across a panel of 35 SSA countries from 1995 to 2018. The data utilized are sourced from the World Development Indicators (2021) and the United Nations Development Program (UNDP) database (2021). Findings – The results reveal that domestic investment has a positive impact on economic development in SSA countries, consistent across all three dimensions of the human development index (income, education and life expectancy). However, external debt exhibits an adverse effect on economic development, consistently yielding negative outcomes for life expectancy, education and income. Practical implications – Based on these findings, the authors recommend that SSA economies implement appropriate policies, such as reducing bureaucratic requirements and addressing corruption, to enhance domestic capital investment. Additionally, efforts should be directed toward channeling contracted debt into productive sectors like road construction and electricity provision. Originality/value – This study is among the first to assess the impact of domestic investment and external debt on the three dimensions of human development outlined by the UNDP. Furthermore, it employs a robust econometric method that considers cross-sectional dependence (CD).